2020
DOI: 10.1101/2020.07.13.200618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complex plant metabolomes guide fitness-relevant foraging decisions of a specialist herbivore

Abstract: Plants produce complex mixtures of primary and secondary metabolites. Herbivores use these metabolites as behavioral cues to increase their fitness. However, how herbivores integrate primary and secondary metabolites into fitness-relevant foraging decisions in planta is poorly understood. We developed a molecular manipulative approach to modulate the availability of sugars and benzoxazinoid secondary metabolites as foraging cues for a specialist maize herbivore, the western corn rootworm. By disrupting benzoxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 114 publications
0
6
0
Order By: Relevance
“…In this work, we found that T. harzianum triggered the release of the root terpenes α‐cubebene and (±)‐camphor and induced the emission de novo of β‐caryophyllene with respect to control plants. A similar response in the emission of volatile sesquiterpenes was identified in maize roots attacked by D. virgifera virgifera .3 Herbivore arthropods use chemosensory receptors to perceive plant‐derived chemical signals and to locate suitable plants and avoid unsuitable plants as hosts 37,40 . In particular, D. virgifera virgifera behaves according to different chemical signals that include CO 2 , aromatic organic compounds and volatile terpenes 37 .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In this work, we found that T. harzianum triggered the release of the root terpenes α‐cubebene and (±)‐camphor and induced the emission de novo of β‐caryophyllene with respect to control plants. A similar response in the emission of volatile sesquiterpenes was identified in maize roots attacked by D. virgifera virgifera .3 Herbivore arthropods use chemosensory receptors to perceive plant‐derived chemical signals and to locate suitable plants and avoid unsuitable plants as hosts 37,40 . In particular, D. virgifera virgifera behaves according to different chemical signals that include CO 2 , aromatic organic compounds and volatile terpenes 37 .…”
Section: Discussionmentioning
confidence: 80%
“…Glucose and sucrose as components of plant sugar blends have been shown to stimulate insect feeding 5 . In fact, the western corn rootworm ( Diabrotica virgifera virgifera ) prefers to feed on roots with a higher carbohydrate content 37 . As products derived from photosynthesis, carbohydrates are the principal source of stored energy for both plants and herbivorous arthropods 5 .…”
Section: Discussionmentioning
confidence: 99%
“…All data were analysed using SPSS 20.0 software. GRLHs feeding preference data were analysed by Wilcoxon's signed-ranks tests (Hu et al, 2020;Machado et al, 2020). A non-parametric test (Friedman-ANOVA, p < .05) for dependent data on olfactory behaviour assays of GRLHs, including plant odour preference and individual compounds was used, and differences attributed to fields using Wilcoxon-Wilcox as a post-hoc test (Faucher, Forstreuter, Hilker, & de Bruyne, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the application of the Fe(III)(DIMBOA) 3 complex on rice or barley, two non-host plant species for the WCR, was sufficient to trigger WCR feeding [ 41 ]. Experiments with benzoxazinoid-deficient plants and WCR larvae with impaired capacities to detect sugars confirmed the importance of the individual and combined cues for WCR foraging, but also revealed considerable WCR robustness to disruption of individual cues [ 42 ]. This may complicate attempts to use single cues for foraging disruption.…”
Section: Disrupting Wcr Establishmentmentioning
confidence: 97%